LO SCETTICISMO TRA RAZIONALITÀ E DISILLUSIONE. BERTRAND RUSSELL ED EMIL CIORAN (Analele Universității București. Limba și literatură română, 2025)
This study offers a comparative analysis of the scepticism of Bertrand Russell and Emil Cioran, highlighting two distinct traditions of philosophical scepticism: Academic and Pyrrhonian. While scepticism has long been debated in philosophy, this paper focuseson the complementary epistemological and existential implications of these views in a modern context. Russell represents methodological scepticism, using doubt as a critical tool to pursue more reliable knowledge without falling into absolute relativism. Conversely, Cioran adopts doubt as an existential stance, suspending judgment in line with Pyrrhonian scepticism and questioning the possibility of absolute truth, expressing deep disenchantment with reality and knowledge. In an age dominated by positivism and trust in scientific and media certainties, balancing Russell’s rational scepticism with Cioran’s scepticism of disenchantment offers valuable insight. This tension helps distance us from both dogmatic rationalism and extreme nihilism, providing a fresh perspective on scepticism’s role in contemporary thought.